A prospective study of effectiveness of Mannheim peritonitis index scoring system in predicting the morbidity and mortality in peritonitis due to hollow viscous perforation - Yadav, Sitaram; Suthar, Ramesh; Meena, Rajaram; Meena, R. S. (International Surgery Journal, 2020)
Background: Peritonitis is defined as inflammation of the peritoneal cavity, caused by a number of etiologic agents including bacteria, fungi, viruses, chemical irritants, and foreign bodies. The Mannheim peritonitis index (MPI) is one of the simple scoring systems in use that allows the surgeon to easily determine outcome risk. Aims and objective: To estimate outcome of patients with perforation peritonitis. To evaluate effect of MPI score in identification of high risk cases. Methods: A prospective study was conducted in 100 patients with peritonitis due to hollow viscous perforation at surgical unit of tertiary care unit. The duration of study was 2 years. All the data was recorded. Written informed consent was obtained and data was analyzed using appropriate analysis strategy. Results: In this study, total 100 patients enrolled, out of which 54 % patients were in the age group <50 years and 46% patients were in the age group >50 years. Mortality was higher among patients with age group more than 50 years (21%) and in female patients (37.93%). 18 patients had organ failure. 87 patients had preoperative duration was >24 hours. 93% patients had non-colonic origin of sepsis. In 52 (52%) patients total MPI score was <21 while 25 (25%) patients total score was 21-29 and it was >29 in 23 (23%) patients. Mortality was higher among patients with MPI Score more than 29 (95.65%). Conclusions: MPI is accurate to be used with patients with peritonitis and should be considered reliable and simple reference for estimating their risk of death. This study differs in one adverse outcome variables, non-colonic origin of sepsis, we advocate need for further studies on Mannheim peritonitis index to include colonic origin of sepsis.